Emergent consilience among coeval fishing and farming communities of the middle holocene on the North Peruvian coast - Dillehay, Tom D.; Tham, Teresa Rosales; Vázquez, Victor; Goodbred, Steve; Chamberlain, Elizabeth; Rodríguez, Gabino (Frontiers in Earth Science, 2022)
Coasts are dynamic, constantly changing ecosystems offering rich and varied foods and other resources. Compared with the monistic structure of crop production in many terrestrial parts of the world, some coastlines reflect a dualistic structure with complementary maritime and agricultural economies beginning in early prehistoric times. In particular, the Pacific coast of the Central Andes offers one of the world’s most abundant and diverse supplies of marine resources. The late Pleistocene to middle Holocene (~ 14,000-4000 cal BP) cultural sequences from south Ecuador to north Chile vary appreciably from one region to the next, but all reveal varying degrees of mixed diets of maritime and terrestrial foods. By ~7000-6500 cal BP, a diversity of seafood and domesticated crops were mutually exchanged to form varied specialized and unspecialized economies in a few Andean regions. This study reports on interdisciplinary data from archaeological sites with mixed economies along the desert coast of the Chicama Valley in north Peru, specifically the Huaca Prieta area dating between ~14,500 to 3800 cal BP. In this area, a dual maritime and agriculture economy developed simultaneously with social differentiation between public ritual monuments and outlying domestic sites in a unique environment of rich marine resources and fertile estuarine wetlands. This and other coastal areas played an important and persistent early role in human population growth and proto-state development in the Andes.